2021
DOI: 10.1039/d1cc01868j
|View full text |Cite
|
Sign up to set email alerts
|

An alginate-confined peroxygenase-CLEA for styrene epoxidation

Abstract: Oxyfunctionalisation reactions in neat substrate still pose a challenge for biocatalysis. Here, we report an alginate-confined peroxygenase-CLEA to catalyse the enantioselective epoxidation of cis-β-methylstyrene in a solvent-free reaction system achieving...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Admittedly, the reaction presented here is not (yet) applicable for commercial-scale synthesis of the bulk chemical KA-oil. Significant improvements in process analytics (such as the quantification of the starting material and in situ H 2 O 2 quantification to adjust the H 2 O 2 dosing), substrate loading (e.g., by using two-liquid phase systems of ideally achieving solvent-free reaction conditions), and improving the catalyst usage (e.g., by further improving the H 2 O 2 -addition strategy) to minimize its cost contribution will be necessary to render the proposed biocatalytic oxyfunctionalization of cyclohexane industrially relevant. However, we are convinced that simple measures such as an adjusted ratio of H 2 O 2 feed rate and Aae UPO concentration and in situ product removal will enhance the productivity and catalyst usage significantly.…”
Section: Resultsmentioning
confidence: 99%
“…Admittedly, the reaction presented here is not (yet) applicable for commercial-scale synthesis of the bulk chemical KA-oil. Significant improvements in process analytics (such as the quantification of the starting material and in situ H 2 O 2 quantification to adjust the H 2 O 2 dosing), substrate loading (e.g., by using two-liquid phase systems of ideally achieving solvent-free reaction conditions), and improving the catalyst usage (e.g., by further improving the H 2 O 2 -addition strategy) to minimize its cost contribution will be necessary to render the proposed biocatalytic oxyfunctionalization of cyclohexane industrially relevant. However, we are convinced that simple measures such as an adjusted ratio of H 2 O 2 feed rate and Aae UPO concentration and in situ product removal will enhance the productivity and catalyst usage significantly.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, researchers started to investigate UPO-catalyzed reactions in organic media, 25 and first attempts for product intensification were already made by the immobilization of AaeUPO. [26][27][28][29] Recently, Tonin et al reported on a pilot-scale production of AaeUPO. 30 Remarkably, 170 g of pure enzyme was produced in 2500 L of fermentation broth after six days and 5 g L −1 of (R)-1phenylethanol was successfully produced for seven days in a 100 mL-scale, batch-wise operated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that nucleophilic amino acid residues such as histidine or cysteine can coordinate to transition metal centres resulting in a mutual inhibition of both, the enzymes and the metal catalysts [25] . It is worth mentioning here that both, 1 and r Aae UPO are intrinsically stable under the given experimental conditions [15,26] . Catalyst 1 can be used even under acid and strong oxidising condition, despite its stability is somewhat reduced [18c] .…”
Section: Resultsmentioning
confidence: 90%
“…[25] It is worth mentioning here that both, 1 and rAaeUPO are intrinsically stable under the given experimental conditions. [15,26] Catalyst 1 can be used even under acid and strong oxidising condition, despite its stability is somewhat reduced. [18c] Incubation of either of 1 and rAaeUPO alone in buffer resulted in no significant reduction of their catalytic activity over several days.…”
Section: Resultsmentioning
confidence: 99%